Modeling and Molecular Spectroscopic Analyses of Cellulose - Mahmoud, Abdel Aziz; Osman, Osama; El-hotaby, Walid; Fakhry, Ahmed; Aziz, Zainab Abdel; Ibrahim, Medhat; Elhaes, Hanan (Journal of Applied Solution Chemistry and Modeling, 2014)
Cellulose is the most abundant biopolymer which is a topic of extensive research work. In this study Fourier Transform Infrared Spectroscopy (FTIR) was utilized to assign the molecular structure of cellulose. B3LYP at 3-21g**, 6-31g** and LANL1DZ then MP2 at 6-31g* levels of theories were conducted to compare the calculated vibrational spectra with the FTIR spectrum. Model molecules of cellulose starting with monomer up to cellulose 18 units were studied with PM3 semiemperical method in order to follow up the effect of polymerization upon some selected physical parameters. Results indicate that final heat of formation and band gap energy have decreased with increasing cellulose units while total dipole moment has increased with increasing cellulose units. It is concluded that the reactivity of cellulose has increased with increasing the units also the unique hydrogen bonding dedicates cellulose to several applications.